Hedging In Ted Talks: A Corpus-Based Pragmatic Study - Tri Nuraniwati; Alfelia Nugky Permatasari (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2021)
Hedging is a communicative strategy and a form of pragmatic competence which plays a central role in delivering the intended message of the speaker. Commonly observed in two-way conversations, hedges as hedging devices are also present in monologues. This study investigates the most common hedges used in popular monologues TED Talks as well as observes the various communicative strategies they denote. 130 transcripts of the talks, taped from 2002-2019 taken from the official website of TED (ted.com), are collected to build a corpus of 337,302 tokens. Through corpus-based analysis using concordance software AntConc 3.5.0, 48 most common hedges are inserted for frequency search. The search hits show that the most frequently-used hedges in the corpus are ‘just,’ ‘could,’ ‘you know,’ ‘actually,’ ‘I think,’ and ‘kind of’ with the numbers of occurrence 1107, 554, 541, 530, 390, and 309 respectively. From the analyses of the functions of the most frequent hedges, it can be concluded that each of the hedges serves distinctive pragmatic strategy which contributes in the communicative processes of the talks.